Some Notes On The Idea Of Living Human Document And Its Implications For Pastoral Praxis - Alokasih Gulo (Eduvest - Journal of Universal Studies, 2022)
This article provides a review of the literature on the concept of a living human document, which was first proposed by Anton T. Boisen and then advanced by Charles V. Gerkin. I will apply a holistic approach to understanding the idea of a living human document in light of the increasingly complicated difficulties humans face in our modern day. In this article, I argue that taking a holistic perspective will help us better comprehend persons in their environments (internal and external contexts). This, as I call it, is an attempt at holistic pastoral theology based on living human document.